Low Levels of Factor H Family Proteins During Meningococcal Disease Indicate Systemic Processes Rather Than Specific Depletion by Neisseria meningitidis - van Beek, Anna E.; Pouw, Richard B.; Wright, Victoria J.; Sallah, Neneh; Inwald, David; Hoggart, Clive; Brouwer, Mieke C.; Galassini, Rachel; Thomas, John; Calvo-Bado, Leo; Fink, Colin G.; Jongerius, Ilse; et al. (Frontiers in Immunology, 2022)
Neisseria meningitidis, the causative agent of meningococcal disease (MD), evades complement-mediated clearance upon infection by ‘hijacking' the human complement regulator factor H (FH). The FH protein family also comprises the homologous FH-related (FHR) proteins, hypothesized to act as antagonists of FH, and FHR-3 has recently been implicated to play a major role in MD susceptibility. Here, we show that the circulating levels of all FH family proteins, not only FH and FHR-3, are equally decreased during the acute illness. We did neither observe specific consumption of FH or FHR-3 by N. meningitidis, nor of any of the other FH family proteins, suggesting that the globally reduced levels are due to systemic processes including dilution by fluid administration upon admission and vascular leakage. MD severity associated predominantly with a loss of FH rather than FHRs. Additionally, low FH levels associated with renal failure, suggesting insufficient protection of host tissue by the active protection by the FH protein family, which is reminiscent of reduced FH activity in hemolytic uremic syndrome. Retaining higher levels of FH may thus limit tissue injury during MD.